2021
DOI: 10.3389/fpubh.2021.757466
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Childhood Experiences and Depressive Symptoms Among Chinese Undergraduates: A Moderated Mediation Model Examining the Roles of Uncertainty Stress and Family Relationship

Abstract: Background: The evidence on the association between benevolent childhood experience (BCE) and depressive symptoms in students is complex. This study aims to explore the underlying mediation mechanism of BCE toward depressive symptoms and whether this link was moderated by the family relationship among Chinese undergraduates.Methods: From March 2021 to May 2021, a cross-sectional study was conducted in China, and 1821 undergraduates were recruited in this study. Participants were asked to complete a self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…A study conducted in rural areas of Southwest China among 490 women has revealed that family function had a direct negative correlation with perinatal depression (Huang et al 2021 ). Moreover, a study conducted in China with 1821 undergraduates indicated that the association between the uncertainty stress and depressive symptoms was significantly moderated by family relationships (Zhang et al 2021 ). However, whether family relationship plays a moderate role between pregnancy specific stress and depressive symptoms has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in rural areas of Southwest China among 490 women has revealed that family function had a direct negative correlation with perinatal depression (Huang et al 2021 ). Moreover, a study conducted in China with 1821 undergraduates indicated that the association between the uncertainty stress and depressive symptoms was significantly moderated by family relationships (Zhang et al 2021 ). However, whether family relationship plays a moderate role between pregnancy specific stress and depressive symptoms has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that those who report more BCEs in childhood have better mental health ( 25 ). Furthermore, one cross-sectional study of Chinese university students shows that BCEs are negatively associated with uncertainty stress and provide a buffer for uncertainty stress ( 26 ). Hou et al also found that Chinese university students who experienced more BCEs were less likely to have uncertainty stress ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…BCEs are common, with the average number ranging from 8.15 to 8.97 in college student and other adult samples in the US (Crandall et al, 2019;Doom et al, 2021;Rodriguez et al, 2021). In contrast to ACEs, BCEs have been associated with better mental health in adulthood, including fewer PTSD symptoms in pregnant women with histories of childhood adversity (Narayan et al, 2018), and fewer symptoms of depression (Doom et al, 2021;Xu et al, 2022;Zhang et al, 2021) and anxiety (Rodriguez et al, 2021;Xu et al, 2022) in university students. While this is a newer research area than ACEs, studies show an opposite pattern of relationship with various psychopathological symptoms, raising the possibility BCEs are a transdiagnostic protective factor for mental disorders, i.e., a factor that decreases the likelihood of experiencing a range of disorders (Lynch et al, 2020).…”
mentioning
confidence: 99%
“…BCEs have also been examined with regard to main/direct effects on outcomes, conceptualized as promotive factors that have favorable main effects on outcomes independent of level of ACEs (e.g., Doom et al, 2021;Narayan et al, 2018;Zhang et al, 2021). In addition, researchers have investigated the neutralizing or protective or buffering role of BCEs on the negative mental health effects of ACEs; however, findings were inconsistent in studies of US university students during the pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation